HUBUNGAN KECACINGAN DENGAN STATUS GIZI PADA MURID SEKOLAH DASAR DI KABUPATEN BOLAANG MONGONDOW UTARA - Anthonie, Romario M.; Mayulu, Nelly; Onibala, Franly (JURNAL KEPERAWATAN)
Abstract: Nutritional status is a health status that produced by a balance between the needs and nutrient inputs. The nutritional status is important because it is a risk factor for the occurrence of morbidity and mortality. In the expanding country like Indonesia, there are some things that can affect a child's nutritional status is low food intake and infectious diseases. The helminthes diseases is the chronicle and endemic disease wich most attached children under five and primary school child age. The aim of this research is to know association helminth with nutritional status of Elementary School child in regency of North Bolaang Mongondow. This research programme is Cross Sectionl Study. The population of this research are all of the Elementary school student of Regency of North Bolaang Mongondow with the population number are 2388 childrens. The sample of this research are 110 student through Proporsional Random Sampling method. To know association of helmints disease with nutritional status of the Elementary School student in Regency of North Bolaang Mongondow, the data analyzed using computerization system, that is Sofware Statistic Program for Social Science (SPSS) version 19.0 through Chi Square (X²) test, with level of significance 95% (α 0,05). The statistic analisis result show which there is no relation between helminthes disease and the Elemntary School student nutritional status in Regency of Norh Bolaang Mongondow,   p = 0,322 (p>0,05). Writer advice, the Elementary School in Regency of North Bolaang Mongondow should be able to cooperate with the around Puskesmas in order to give illumination about nutrient balancing compiled to decrease deficiency that happened to Elementary School student in Regency of North Bolaang Mongondow. Keywords: helminths disease, nutritional status Abstrak : Status gizi ialah suatu status kesehatan yang dihasilkan oleh keseimbangan antara kebutuhan dan masukan nutrient. Status gizi ini menjadi penting karena merupakan faktor resiko untuk terjadinya kesakitan dan kematian. Di negara yang sedang berkembang seperti Indonesia, ada beberapa hal yang dapat mempengaruhi status gizi anak yaitu konsumsi makanan yang kurang dan penyakit penyerta seperti infeksi (Waryana, 2010). Kecacingan merupakan penyakit endemik dan kronik yang diakibatkan oleh cacing yang paling banyak menyerang balita dan anak usia sekolah dasar. Tujuan penelitian ini adalah untuk mengetahui hubungan kecacingan dengan status gizi pada Murid Sekolah Dasar di Kabupaten Bolaang Mongondow Utara. Rancangan penelitian ini adalah seluruh murid Sekolah Dasar di Kabupaten Bolaang Mongondow Utara dengan besar populasi 2388. Sampel dalam penelitian ini adalah sebanyak 110 orang dengan menggunakan metode Proporsional Random Sampling. Untuk melihat hubungan antara kecacingan dengan status gizi pada Murid Sekolah Dasar di Kabupaten Bolaang Mongondow Utara, data dianalisis dengan menggunakan system komputerisasi, yaitu Software Statistic Program for Social Science (SPSS) versi 19.0 dengan  menggunakan uji chi-square (X²), pada tingkat kemaknaan 95% (α 0,05). Analisis statistic menunjukan hasil bahwa tidak ada hubungan antara kecacingan dengan status gizi pada murid sekolah dasar di Kabupaten Bolaang Mongondow Utara. p= 0.322 (p>0,05).Saran penulis, sebaiknya sekolah-sekolah dasar di Kabupaten Bolaang Mongondow Utara dapat bekerja sama dengan puskesmas setempat untuk member penyuluhan tentang pemenuhan gizi seimbang untuk menekan angka gizi kurang yang terjadi pada siswa-siswa sekolah dasar di Kabupaten Bolaang Mongondow Utara Kata Kunci : Kecacingan, Status Gizi